Research on the Space Design and Planning of Natural Landscape Architecture Based on Virtual Reality Technology - Shu, Jiang (Journal of physics. Conference series, 2021)
VR tech can build a realistic space scene, ameliorate the sense of human-computer interaction and experience, realize the effective and vivid simulation of the architectural space scene, so as to stimulate and release the imagination and creativity of designers, so it has important research value. Based on this, this paper first analyses the architecture of VR system, then studies the utilization of VR tech in natural landscape architectural space design and planning, and finally gives the process of architectural planning and design based on VR.